Empathy, place and identity interactions for sustainability. (May 2019) - Brown, Katrina; Adger, W. Neil; Devine-Wright, Patrick; Anderies, John M.; Barr, Stewart; Bousquet, Francois; Butler, Catherine; Evans, Louisa; Marshall, Nadine; Quinn, Tara
Highlights: Proposes empathy as a key phenomenon that shapes human-environment relations. Empathy-sustainability involves empathy with others and empathy with nature, mediated through place and identity. Diverse methods, from experiments and games through to creative engagement, can measure and stimulate empathy. Evidence on empathy-sustainability relationship, and the mediating roles of place and identity, informs policy on sustainability. Abstract: Sustainability science recognises the need to fully incorporate cultural and emotional dimensions of environmental change to understand how societies deal with and shape anticipated transformations, unforeseen risks and increasing uncertainties. The relationship between empathy and sustainability represents a key advance in understanding underpinning human-environment relations. We assert that lack of empathy for nature and for others limits motivations to conserve the environment and enhance sustainability. Critically, the relationship between empathy and sustainability is mediated by place and identity that constrain and shape empathy's role in pro-environmental sustainability behaviour. We review emerging evidence across disciplines and suggest a new model exploring interactions between place, identity and empathy for sustainability. There are emerging innovative methodological approaches to observe, measure and potentially stimulate empathy for sustainability.